Carbapenemase-Producing Enterobacterales - Andreoni, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Carbapenem-resistant Enterobacterales (CRE) are a common cause of infections in both community and healthcare settings and have become an increasing threat to public health worldwide. The focus of this Special Issue includes aspects concerning plasmid-mediated antimicrobial resistance along with other carbapenem resistance mechanisms. Understanding the prevalence and routes of transmission of CRE is important in developing specific interventions for healthcare facilities, as well as the general impact of CRE circulation on the environment. Attention has also been focused on carbapenemase testing in order to provide advanced phenotypic and molecular assays for the identification of CRE, as a valid tool for active global surveillance, and from this perspective, the study of resistance mechanisms can provide significant support for the development of new and appropriate antimicrobial molecules. For all of these reasons, the phenomenon of carbapenem resistance deserves more attention, for the sake of public health.